التعويض عن الضرر غير المتوقع بين المسؤولية العقدية والمسؤولية التقصيرية دراسة مقارنة بين القانون المدني الليبي والفقه الإسلامي - هبري، عبير محمد موسى (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
This study aims to assess the Libyan legislators policy regarding compensation, especially for the damages that contractors do not anticipate. This issue is not addressed in Libyan law, in accordance with contractual responsibility, except in the case of a fraud or gross error by the contractor. This is to determine the shortcomings and deficiencies in compensating unexpected damages according to the contractual responsibility, as well as analysing the most important principles that govern this issue within its general framework. These principles include having no prejudice towards others, no abuse of rights and the autonomy of will. The study also aims to determine how to compensate for unexpected damages that occur in good faith by contractors. The study used the appropriate scientific methods such as the analytical method to analyses the relevant legal provisions as well as the comparative method to compare between the legal provisions and the provisions of Islamic Shariah in order to reach a solution where Shariah law is a key source. The study also follows a critical approach to assess some juristic views, while the inductive approach is used to find solutions for the issue of compensation for damages in general and the unexpected damages in particular. The results indicate that there is a significant difference between compensation law in Libya and Islamic law. It also indicates that there is a confusion among some scholars of law regarding the inversion of liability from a contractual to a tortious liability in cases of fraud and gross error. It also indicates the possibility of compensation or assurance for a damage even if not expected when a contract is still in place. The study recommends the need to fill the gap in Libyan civil law by proposing a new provision that handles this issue, which will be consistent with the rest of the provisions and key principles of civil law. Additionally, existing law could also be amended. It also recommends to state to review the legal articles that govern provisions of civil liability to find some kind of proportionality and consistency between provisions, which may lead to the development of a separate special law apart from civil law that regulates only the provisions of civil liability, both contractual and tortious. Finally, the study recommends that Libyan law fully follow Shariah law to review and modify the provisions from time to time in line with the rules of the Divine Law. This will help create an integrated legal system which is parallel with Shariah law which organises all aspects of social, political, legal and economic life, with the achieve aim to a more just, balanced and powerful legal system capable of solving all legal problems that arise from transactions between individuals and stability in financial transactions and commitments.